Education to inhabit the contemporary world: perceptions of students in Catholic schools - Eder D'Artagnan Ferreira Guimarães; Pedro Dabin (Pontifícia Universidade Católica de Campinas, 2021)
This article analyzes part of the data collected in a doctoral research on the place of Catholic schools in the contemporary educational scenario, based on the perception of various actors in education: managers, educators, pastoralists and students. Linked to the National University of Rosario, Argentina, the research defines as one of its objectives to problematize the perceptions of High School students about their experience of schooling. 157 students from 6 Catholic schools in Belo Horizonte/MG presented their perceptions of school life through a written questionnaire and a drawing. The data were analyzed using Qualitative Epistemology and its concept of subjective meanings. Based on their experience in the Catholic school, students evaluate how the plastered educational system prevents the development of more integral educational and focused on human development processes; report the traditionalism that runs through schooling today; demonstrate difficulty in identifying the school's contribution to their formation and definition of life project; and attribute different meanings to school education, according to their trajectory in the Catholic school.